Application of The PjBL Model to Train Science Literacy Skills of High School Students on the Subject of Alternative Energy - Putri Indah Ramadhani; Rif'ati Dina Handayani; Lailatul Nuraini; Leizy Free Agustin F. (Berkala Ilmiah Pendidikan Fisika, 2023)
The development of science and technology in the era of the Industrial Revolution 4.0 requires everyone to master 21st-century skills, one of which is science literacy. Science literacy skills in Indonesia are still relatively low. Students' low science literacy skills are caused by several factors: the selection of learning models, teaching materials, and non-contextual learning. This study aims to describe the application of the PjBL model to train high school students' science literacy skills on the subject of alternative energy. This research uses descriptive qualitative research. The sampling technique in this study used a purposive sampling technique. The research instruments used in this study were observation sheets for implementing the learning model and student worksheets. The qualitative data analysis technique used in this research is a case study. The results showed that implementing learning conducted in groups could make students active in solving problems. Each group actively participated in answering student worksheets and completing projects by analyzing and making alternative solutions to the problems presented. The stages in the student worksheet following the PjBL model can shape the science literacy skills of high school students. This study's conclusion shows that applying the PjBL model trains students' science literacy skills. While applying the PjBL model, researchers directed each group to carry out project activities through the learning stages of the PjBL model. Each group was able to identify and provide solutions to problems, design product plans, develop schedules, make simple projects following the design, test the results, and make conclusions.